2014
DOI: 10.1021/ic502426x
|View full text |Cite
|
Sign up to set email alerts
|

Raman and IR Studies of Pressure- and Temperature-Induced Phase Transitions in [(CH2)3NH2][Zn(HCOO)3]

Abstract: Temperature- and pressure-dependent studies of Raman and IR spectra have been performed on azetidinium zinc formate, [(CH2)3NH2][Zn(HCOO)3]. Vibrational spectra showed distinct anomalies in mode frequencies and bandwidths near 250 and 300 K, which were attributed to structural phase transitions associated with the gradual freezing of ring-puckering motions of the azetidinium cation. Pressure-dependent studies revealed a pressure-induced transition near 0.4 GPa. Raman spectra indicate that the structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…4) to librations of formate ions, whereas these bands observed near 60 cm -1 -to T'(EtA + ) and L(EtA + ) modes. We also attribute the 194-300 cm -1 bands to translational motions of HCOO -, which is in agreement with former studies of other metal-formate frameworks [30,[34][35][36].…”
Section: Spectra Of the Polycrystalline Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…4) to librations of formate ions, whereas these bands observed near 60 cm -1 -to T'(EtA + ) and L(EtA + ) modes. We also attribute the 194-300 cm -1 bands to translational motions of HCOO -, which is in agreement with former studies of other metal-formate frameworks [30,[34][35][36].…”
Section: Spectra Of the Polycrystalline Samplessupporting
confidence: 92%
“…3) since several lattice modes depend significantly on mass and size of ions building the structure. [30,[34][35][36]. For that reason, we assigned the strong Raman bands in the 139-190 cm -1 spectral range (Fig.…”
Section: Spectra Of the Polycrystalline Samplesmentioning
confidence: 99%
“…A quite unusual feature of this material is that the high‐temperature phase is metastable on cooling (phase transition is irreversible) and the backward phase can be restored only by high pressure . It is worth adding that although presence of structural changes in MOFs is fairly common, two temperature‐induced phase transitions were rarely observed for metal formate frameworks, that is, beyond aforementioned EtAMg, such behavior was reported for [(CH 2 ) 3 NH 2 ][Zn(HCOO) 3 ] with azetidinium cations as templates (T c1 = 299 K, T c2 = 254 K) …”
Section: Introductionmentioning
confidence: 88%
“…As a consequence, an investigation of behavior of MOFs in response to this external stimulus is necessary, especially from the application point of view. Up to date, a few papers reported high pressure studies of chiral, perovskite and niccolite metal formate frameworks. These studies revealed presence of pressure‐induced transformations and negative linear compressibility for some compounds.…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Li et al 10 have successfully synthesized the Ln-formate MOF, namely [tmenH2][Er(HCOO)4]2 (tmenH2 2+ = N,N,N',N'tetramethylethylenediammonium) with pillared-layer type structure. [13][14][15] PIPTs are both scientifically interesting and technologically important as the product phase may have properties that are substantially different from those of the parent phase. It behaves as a paramagnet in zero field and displays interesting field-induced ac-susceptibilities and slow magnetic relaxation that most likely originates from the spin-lattice relaxation.…”
Section: Introductionmentioning
confidence: 99%